Spanish National Cinema. - Triana-Toribio, Núria (National cinemas series., 2012)
This study examines the discourses of nationalism as they intersected or clashed with Spanish film production from its inception to the present. While the book addresses the discourses around filmmakers such as Almodóvar and Medem, whose work has achieved international recognition, Spanish National Cinema is particularly novel in its treatment of a whole range of popular cinema rarely touched on in studies of Spanish cinema. Using accounts of films, popular film magazines and documents not readily available to an English-speaking audience, as well as case studies focusing on the key issues of.